Filtration to Reduce Turbidity, Manganese, and Iron Concentrations in Polluted Groundwater Sources - Arson, Rudolfus; Ratnawati, Rhenny; Febrianti, Aulia Nur (Journal of Earth Energy Science, Engineering, and Technology, 2025)
The Indonesian people use most clean water from groundwater. The issue that develops is that Manganese (Mn), Iron (Fe) and Turbidity frequently taint the quality of groundwater and river water used by the population. To lower the concentration of Manganese (Mn), Iron (Fe) concentration and turbidity levels in groundwater in the Rungkut area of Surabaya, this study will apply filtering technology comprising silica sand, manganese zeolite and ferrolite media with varying media height.  From the research that has been done, it is known that combination A filtration technology has the ability to reduce the concentration of Manganese (Mn) by 86.96%, Iron (Fe) by 65.87% and the turbidity level by 86.03% while combination B has the ability to reduce the concentration of Manganese (Mn) by 68.12%, Iron (Fe) by 76.19% and the turbidity level by 72.23% and combination C has the ability to reduce the concentration of Manganese (Mn) by 26.09%, Iron (Fe) by 78.57% and the turbidity level by 88.48%.  The study found that combination A filtration technique most effectively lowers the Manganese (Mn) content by 86.96%, combination C does so for iron (Fe) by 78.57% and the turbidity level by 88.48%.